In-house, university-based work experience vs off-campus work experience. Issue 3 (14th August 2017) - Forsyth, Jacky; Cowap, Lisa
Abstract : Purpose: The purpose of this paper is to investigate students' perceptions of the value, impact, benefits and disadvantages of in-house, university-based work experience vs off-campus work experience. Design/methodology/approach: Three focus groups, one consisting of students who had undertaken work experience off-campus at an employers' workplace ( n =6), one consisting of students who had undertaken work experience in-house with a university-based employer ( n =6), and a third mixed group ( n =6, consisting of students who had undertaken both types), were formed. Focus group data were supplemented by interviews ( n =3). Data were transcribed and analysed thematically. Findings: Based on student perceptions, both types of work experience were thought to: enhance future employment; provide career insight; enable skill/experience acquisition and application; and be useful for building relationships. Work experience that occurred in-house was, in addition, perceived to be cost effective; enabling students to be more closely supervised and supported; good for relationship building between and within students/staff; beneficial for increasing student attainment; and enabling students to see the link between theory and practice more clearly. In-house work experience was, however, deemed to be restricted in terms of variety, and links with and perceptions of external stakeholders. Research limitations/implications: The study is limited in that it is based on the perceptions of students undertaking unique types of integrated work experience within one faculty at one university. Practical implications: When deciding on whether in-house or off-campus work experiences are offered, consideration should be given to level of support, supervision, observation, and travel and time costs. Originality/value: Original views of students regarding in-house work experience have been gathered, which can be used to inform in-course workplace practices.